Development and Validation of a Stability-Indicating RP-HPLC Method for the Simultaneous Determination of Palonosetron and Fosnetupitant - G. Sai Charan,; M. Akiful Haque, (The Bioscan, 2025)
A simple, accurate, and robust RP-HPLC method was developed and validated for the simultaneous estimation of Palonosetron (PST) and Fosnetupitant (FST) in Akynzeo I.V. formulation. Chromatographic separation was achieved using a Waters C18 column (250 × 4.6 mm, 5 μm) with a mobile phase of K2HPO4 buffer: Acetonitrile (70:30 v/v) at a flow rate of 1.0 mL/min, and a detection wavelength of 228 nm. PST and FST exhibited retention times of 1.76 min and 2.31 min, respectively. Linearity was observed within 0.125–0.375 μg/mL for PST and 117.5–352.5 μg/mL for FST. The developed method was validated as per ICH Q2(R1) guidelines and was found precise, accurate, specific, and stability-indicating.